1991
DOI: 10.2105/ajph.81.8.1052
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for childhood homicides in Ohio: a birth certificate-based case-control study.

Abstract: Death certificate of children less than 8 years of age who were killed between 1979 and 1986 were linked to their Ohio birth certificates and compared with those of Ohio children born in 1983 (controls). Having an unmarried mother increased risk of homicide almost fivefold (odds ratio 4.87). Having a teenage mother, a mother who had not graduated from high-school, and being of Black race or low birthweight each increased the risk by approximately threefold. Increases in the proportion of children born to unmar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…[3][4][5] However, methodologic challenges in child maltreatment research have hampered identification of important risk factors and the development of effective prevention strategies. 6 Several studies have identified the following maternal risk factors for fatal child maltreatment and child homicide 3,5,[7][8][9][10][11][12][13] : young maternal age, 3,5,8,9,12,13 Ͻ12 years of maternal education, 3,5,8,9 late or no prenatal care, 3,5,9,12,13 unmarried parents, 3,8,9,12 black race, 3,5,12,13 and higher parity. 13 Child characteristics that are risk factors include male gender 9,13 and low birth weight.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] However, methodologic challenges in child maltreatment research have hampered identification of important risk factors and the development of effective prevention strategies. 6 Several studies have identified the following maternal risk factors for fatal child maltreatment and child homicide 3,5,[7][8][9][10][11][12][13] : young maternal age, 3,5,8,9,12,13 Ͻ12 years of maternal education, 3,5,8,9 late or no prenatal care, 3,5,9,12,13 unmarried parents, 3,8,9,12 black race, 3,5,12,13 and higher parity. 13 Child characteristics that are risk factors include male gender 9,13 and low birth weight.…”
mentioning
confidence: 99%
“…13 Child characteristics that are risk factors include male gender 9,13 and low birth weight. 3,7,8,12 Previously documented maltreatment is a strong risk factor for child homicide. 10,11 These studies are limited by their lack of information on household composition at the time of the child's death.…”
mentioning
confidence: 99%
“…Although previous reports, [5][6][7][8] have shown low birth weight to be a risk factor for both infant homicide and unintentional injury, its association independent of race has not been examined. Because birth weight, like race, is highly correlated with other markers of low socioeconomic status, the mechanism leading to fatal injury is not clear.…”
mentioning
confidence: 99%
“…Risk is somewhat higher for males and the perpetrator is most often the mother (Christoffel, 1990;Crittenden & Craig, 1990;Hampton, 1987). Factors contributing to vulnerability for physical abuse and battering death of young children have been identified to include poverty; metropolitan residence; low birth weight; handicapping condition; young unmarried mothers, especially teenagers; mothers with less formal education; and history of abuse in the parent's family (Christoffel, 1990;Crittenden & Craig, 1990;Hampton, 1987;Winpisinger, Hopkins, Indian, Hostelter, 1991).…”
Section: Nature and Characteristics Of Riskmentioning
confidence: 99%